Anmeldelser - Jensen, Niels Martin (Danish Yearbook of Musicology, 1979)
Review of: Seventeenth-Century Instrumental Dance Music in Uppsala University Library Instr. mus. ha 409 (= Monumenta Musicae Svecicae VIII). Transcribed and Edited by Jaroslav J.C. Mrácek. Edition Reimers, Stockholm, 1976.